Current Diagnosis and Therapeutic Approach of Functional Mitral Regurgitation - Prima Almazini (Acta Medica Indonesiana)
Functional mitral regurgitation is characterized by normal structures of the mitral valve and chordae tendinea, but the regurgitation occurs due to geometric changes in the left atrium and left ventricle. This condition can contribute to heart failure progression and lead to a poor prognosis. Functional mitral regurgitation is found in approximately one-third of patients with heart failure with a decreased ejection fraction. Echocardiography is the primary work-up for assessing the anatomy and function of the left ventricle, mitral valve, and severity of functional mitral regurgitation. Additionally, for the latter, an integrated qualitative and quantitative assessment is essential to determine the optimal therapeutic strategy. According to the current guidelines, medical therapy remains the main treatment for functional mitral regurgitation. Yet, transcatheter intervention is a safe and effective treatment option in selected patients. While the effect of surgery on improving mortality in patients with functional mitral regurgitation is not established yet, recent guidelines recommend considering surgery for patients who have undergone coronary artery bypass surgery or other cardiac procedures.